2012
DOI: 10.5142/jgr.2012.36.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean Red Ginseng on Cognitive and Motor Function: A Double-blind, Randomized, Placebo-controlled Trial

Abstract: Ginseng has a long history of use for health enhancement, and there is some evidence from animal studies that it has a beneficial effect on cognitive performance. The purpose of this study was to investigate the effect of Korean red ginseng on cognitive performance in humans. A total of 15 healthy young males with no psychiatric or cognitive problems were selected based on an interview with a board-certified psychiatrist. The subjects were randomly assigned to receive a daily dose of 4,500 mg red ginseng or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Twenty-eight trials originated from Korea [28]–[55], and two trials were conducted in Thailand [26] and the United Kingdom [27]. Sixteen studies [28], [32]–[41], [44]–[47], [53] were published in Korean, and 14 trials [26], [27], [29]–[31], [42], [43], [48]–[52], [54], [55] were written in English.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-eight trials originated from Korea [28]–[55], and two trials were conducted in Thailand [26] and the United Kingdom [27]. Sixteen studies [28], [32]–[41], [44]–[47], [53] were published in Korean, and 14 trials [26], [27], [29]–[31], [42], [43], [48]–[52], [54], [55] were written in English.…”
Section: Resultsmentioning
confidence: 99%
“…The key data from studies in healthy persons are summarised in Table 1 [26]–[34], and the data regarding other various conditions are summarised in Table 2 [35]–[55]. The included RCTs used ginseng powder either in raw (4 studies) [35], [38], [53], [55] or in capsules (22 studies) [26]–[29], [31], [32], [34], [36], [37], [39]–[41], [43]–[48], [50][52], [54] and extract preparation (2 studies) [33], [42], while two studies [30], [49] did not report the preparation type of ginseng. They addressed a wide range of conditions: generally healthy (i.e., studies in healthy individuals) [26]–[34], erectile dysfunction [35]–[40], gastric cancer [41], [43], colon cancer [42], gastrointestinal carcinoma [44], chronic gastritis [45], diabetes mellitus [46], [47], androgenic alopecia [48], coronary artery [49], dry mouth [50], glaucoma [51], obesity [52], metabolic syndrome [53], dyspepsia and indigestion [54] and Alzheimer’s disease [55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, several studies showed that ginseng alleviates motor dysfunction of rats that have undergone spinal cord injury [14] and KRG improves motor and cognitive functions in normal subjects [15], which can be considered a basis of its tonifying effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RG has been shown to improve cognitive function related to the auditory pathway using electrophysiologic evaluation [26]. …”
Section: Discussionmentioning
confidence: 99%